Combining Nuclear and Mitochondrial Loci Provides Phylogenetic Information in the Philopterus Complex of Lice (Psocodea: Ischnocera: Philopteridae). Issue 1 (23rd August 2020) - Najer, Tomas; Papousek, Ivo; Sychra, Oldrich; Sweet, Andrew D; Johnson, Kevin P
Abstract: The Philopterus Complex includes several lineages of lice that occur on birds. The complex includes the genera Philopterus (Nitzsch, 1818; Psocodea: Philopteridae), Philopteroides (Mey, 2004; Psocodea: Philopteridae), and many other lineages that have sometimes been regarded as separate genera. Only a few studies have investigated the phylogeny of this complex, all of which are based on morphological data. Here we evaluate the utility of nuclear and mitochondrial loci for recovering the phylogeny within this group. We obtained phylogenetic trees from 39 samples of the Philopterus Complex (Psocodea: Philopteridae), using sequences of two nuclear ( hyp and TMEDE6 ) and one mitochondrial ( COI ) marker. We evaluated trees derived from these genes individually as well as from concatenated sequences. All trees show 20 clearly demarcated taxa (i.e., putative species) divided into five well-supported clades. Percent sequence divergence between putative species (~5–30%) for the COI gene tended to be much higher than those for the nuclear genes (~1–15%), as expected. In cases where species are described, the lineages identified based on molecular divergence correspond to morphologically defined species. In some cases, species that are host generalists exhibit additional underlying genetic variation and such cases need to be explored by further future taxonomic revisions of the Philopterus Complex.